The Influence of Environmental Factors on the Psychological Growth of Children (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Language is a skill that is naturally acquired by babies. From birth, toddlers are social beings attracted to communication. But over time, the child will emancipate himself from his parents, learning the codes of the outside world by himself, thus promoting his construction towards adult life. In this article we have tried to deal with the topic of the influence of the environment on language learning in children and different factors acting on their psychological development.